2011
DOI: 10.1186/1743-7075-8-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-18: A specific biomarker for atherosclerosis-prone patients with metabolic syndrome

Abstract: BackgroundMetabolic syndrome (MetS) is associated with an increased risk of the development of atherosclerotic cardiovascular disease (CVD). Interleukin-18 (IL-18), which is a pleiotropic proinflammatory cytokine with important regulatory functions in the innate immune response system, plays a crucial role in vascular pathologies. IL-18 is also a predictor of cardiovascular death in patients with CVD and is involved in atherosclerotic plaque destabilization.ResultsIn order to determine if circulating levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 51 publications
(57 reference statements)
1
21
1
1
Order By: Relevance
“…It was postulated that exercise may lower IL-18 concentration via insulin-signaling modification [28]. A significant decrease in the concentration of IL-18 has been observed in cyclists 24 hours after completing a 230 km road race [29]. On the other hand, increased concentrations of IL-18 have been associated with several components of the metabolic syndrome and used as a factor in predicting diabetes, atherosclerosis, and cardiovascular disorders [3032].…”
Section: Discussionmentioning
confidence: 99%
“…It was postulated that exercise may lower IL-18 concentration via insulin-signaling modification [28]. A significant decrease in the concentration of IL-18 has been observed in cyclists 24 hours after completing a 230 km road race [29]. On the other hand, increased concentrations of IL-18 have been associated with several components of the metabolic syndrome and used as a factor in predicting diabetes, atherosclerosis, and cardiovascular disorders [3032].…”
Section: Discussionmentioning
confidence: 99%
“…Dutot et al [27] observed that high glucose induced ROS overproduction in retinal pigment epithelial cells (RPEs). In contrast, Busik et al [28] reported that high glucose does not augment ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested, increase in the serum level of IL-18, as a predictor of progression of diabetic nephropathy and cardiovascular diseases [Nakamura et al, 2005]. Moreover, IL-18 has been also suggested as a useful biomarker of the clinical manifestations of metabolic syndrome and CAD risk factors [Trøseid et al, 2010;Yamaoka-Tojo et al, 2011].…”
mentioning
confidence: 99%